The prognostic impact of right ventricular dysfunction in patients with septic cardiomyopathy. (25th November 2020) - Hiraiwa, H; Kasugai, D; Okumura, T; Kazama, S; Kimura, Y; Shibata, N; Arao, Y; Oishi, H; Kato, H; Kuwayama, T; Yamaguchi, S; Kondo, T; et al.
Abstract: Background: Sepsis is a systemic condition of profoundly impaired health in which an infection leads to a dysregulated host response, and consecutively causes organ dysfunction, shock, and even death. Septic cardiomyopathy (SCM) is one of the multiple organ dysfunctions. SCM is typically defined as left ventricular (LV) dysfunction, presented by decreased LV ejection fraction (LVEF). However, it remains unclear about the detailed mechanism of cardiac dysfunction. In addition, the prognostic impact of right heart dysfunction in SCM patients has not been fully investigated. Purpose: The purpose of this study was to investigate the prognostic impact of right heart dysfunction in patients with SCM. Methods: We used the MIMIC-III (Medical Information Mart for Intensive Care III) critical care database, which is a large, freely-available database comprising deidentified health-related data associated with over forty thousand patients who stayed in critical care units of the Beth Israel Deaconess Medical Center between 2001 and 2012. We retrospectively analyzed data of patients with septic shock on admission to intensive care unit (ICU). Septic shock was defined as the presence of any suspected infections, the need for vasopressors, and the lactate level exceeding 2 mmol/L, based on the Sepsis-3 criteria. Patients were performed portable transthoracic echocardiography (TTE) during hospitalization. LVEF and right ventricular (RV) function were determined predominately by visual estimation in the parasternal long-axis view. SCM was defined as having a minimum LVEF of 50% or less during hospitalization. Patients with hyperdynamic motion of LVEF >70% were excluded. Results: In total, there were 2254 patients with septic shock. Of these, 604 patients who underwent TTE were enrolled, and 314 patients were diagnosed with SCM. At baseline, age, gender, Sequential Organ Failure Assessment (SOFA) score, maximum lactate levels, and maximum norepinephrine dosage were 70 [59–79] years, 194 males, 13 [11–15], 4.0 [2.7–6.2] mmol/L, and 0.20 [0.10–0.31] mcg/kg/min, respectively. All patients were treated with vasopressors. In Kaplan-Meier survival analysis, patients with SCM had increased 28-day mortality compared with those without SCM (log-rank, p=0.09). In addition, we divided SCM patients into two groups; SCM with and without RV dysfunction. SCM patients with RV dysfunction had significant increased 28-day mortality compared with those without RV dysfunction (log-rank, p=0.01) (Figure). In Cox proportional hazard regression analysis adjusted for age, male sex, SOFA score, and maximum lactate levels, RV dysfunction was an independent determinant of 28-day mortality (hazard ratio, 1.59; 95% confidence interval, 1.03–2.46; p=0.03). Conclusions: The presence of RV dysfunction increased 28-day mortality in patients with SCM. It might be useful for predicting the prognosis of SCM to evaluate not only left heart function but also right heart function. Funding Acknowledgement: Type of funding source: None